Your solution, their problem - their solution, your problem. The gordian knot of cultural heritage planning and management at the local government level in Australia. - Spennemann, Dirk H. R. (TH Zürich, NSL, 2006)
Der Beitrag geht den Unterschieden bzw. Gegensätzen zwischen den von der Kommunalpolitik oder der -verwaltung durchgeführten Untersuchungen, Planungen und Unterschutzstellungen von Denkmalen in Australien und den Studien und Listen, die von Denkmalschutz-Experten angefertigt wurden, nach. Hintergrund des Beitrags ist die stetig abnehmende Bedeutung der Top-down-Planungen der Wissenschaftler und das Aufkommen zahlreicher Bottum-up-Untersuchungen aus der lokalen Politik und Verwaltung. Die dabei auftretenden Schwierigkeiten untersucht der Beitrag u.a. anhand der australische ICOMOS Charta und ihrer Kriterien für die Denkmalwürdigkeit, anhand der generellen Schwierigkeiten eines Wertens und Bewertens von Kulturrelikten, der Besonderheiten des kulturellen Erbes der Ureinwohner und der Untrennbarkeit von Natur- und Kulturerbe. Er zeigt, dass in Australien der Aufstellung umfangreicher Listen nur geringe Anstrengungen zum praktischen Schutz von Objekten kulturellen Erbes folgen. goj/difu

Cultural heritage management is, in essence, a facet of social engineering, whereby physical remains of the past (and present) are selectively preserved based on values currently held by the population at large. Indeed, mid- and long-term protection of heritage sites can only occur if such places are "embraced" or "owned" by the community. However, public opinion, often colored by nostalgia, omits, consciously or unconsciously, places that do not fit the present value system. Thus, inevitably, there are places that need to be preserved that are identified by expert opinion, even if a community is apathetic or even antagonistic. Such differences of opinion allow conflicts to occur. Local planning and the implementation of planning priorities are inevitably caught up in it. The political dimension at the Local Government Authority (LGA) level further complicates matters, particularly as we move from one heritage to a multitude of "heritages". Over the past decade, the management of cultural heritage sites at the local government level has seen the decline of top-down, expert-driven studies, while bottom-up, community-driven, or at least community influenced, studies have increased. Both approaches have their failings and lead to gaps in the record. Furthermore, all too often heritage plans are limited. Great effort is expended focusing on the historic trends and themes of an area and on inventorying, evaluating and listing places deemed worth protecting. Yet, next to no effort is spent on implementation strategies, ranging from capacity building, within the administering local government to education of property owners, wider stakeholders, public residents in the LGA and outside visitors. The paper discusses the pitfalls inherent in the various planning approaches and outlines strategies for LGA-level planning and management to maximize returns from heritage planning projects. difu
Keywords: Denkmalschutz; Denkmalpflege; Kultur; Naturdenkmal; Kommunalpolitik; Zielkonflikt; Kulturerbe; Kulturgut